Caracterização físico-química, fenólica e sensorial da CV. Marselan de diferentes regiões do Rio Grande do Sul - Arenhart, Márcia (2015)
There is a great diversity of vines in the world, generating high variability characteristics of the wines produced. With the increased interest motivated by health benefits, making room for the growth of consumption and the grape and wine market potential, the search for varieties able to adapt to different climatic conditions and the growing consumer demand for wine quality, introduces the 'Marselan' piecemeal viticulture scenario. 'Marselan' is a red grape vinifera, obtained by crossing the 'Grenache' and 'Cabernet Sauvignon'. The Rio Grande do Sul has the largest percentage of cultivated area with grape in Brazil, and is the largest producer of wine. The quality of products derived from the grape is dependent on its physicochemical properties and phenolic composition characteristics of cultivars. This study aims to characterize physicochemical the cultivate and the varietal wine, and also describe the sensory profile of the varietal wine Marselan obtained from grapes produced in the regions of the Campanha Gaúcha, Serra Gaúcha and Serra do Sudeste of Rio Grande do Sul. Six samples of grapes produced different regions were collected. Part of berries was frozen in liquid nitrogen and stored in a freezer for further analysis and preparation of extracts, the remainder was used for the microvinification. Analysis of total polyphenols, total flavonoids, procyanidins, tannins, anthocyanins, polymeric pigments, intensity and color tone, color characteristics by the CIE L* a* b* space, acidity, pH, total soluble solids, total sugars (reducing and non-reducing) and antioxidant capacity were performed. The sensory characteristics of the wines were determined by quantitative descriptive analysis with a team of 10 trained panelists. The grape and wine samples Marselan differ in physicochemical parameters evaluated and sensory analysis. Industrial maturation, phenolic ripeness, phenolic compounds and antioxidant capacity data of 'Marselan' demonstrated their adaptability to all regions of Rio Grande do Sul, but are highly dependent on the weather, which provide different features. All red wines are in accordance with the standards established by Brazilian law. The total polyphenol content (2047.07 to 4777.98 mg L-1) and anthocyanins (645.20 874,67mg the L-1) found in a young wine, Marselan presents a good potential for development of guard wines. The antioxidant capacity follows the trend of phenolic compounds. Regarding the color parameters of the wine samples are somewhat different, but it is not possible to characterize differences in the area and its color is characteristic of young wines. The method of quantitative descriptive analysis revealed that the studied samples have distinct sensory profiles, except in the aroma, which indicates the typical characteristics of the cultivar studied for the aromas of red fruits, dried fruits, woody and sweet. The attributes violet color, translucent, fruity flavor, astringency and persistence are the most important to discriminate samples of red wine, however the other attributes as herbaceous aromas, alcohol and floral, bitter flavors, acid and woody, pungency and body help to describe sensorily the cv. Marselan. It is possible to discriminate sensory samples of red wine based on the production region.